A Global Synthesis Suggests Ectomycorrhizal and Arbuscular Mycorrhizal Woody Plants Experience Contrasting Plant–Soil Feedbacks - Xiaoyang Song; Jun Ying Lim; David F. R. P. Burslem (Global Ecology and Biogeography, 2026)
Aim Plant–soil feedbacks (PSFs) are important ecological phenomena that influence plant performance and community assembly. Mycorrhizal fungi, including arbuscular mycorrhizal (AM) and ectomycorrhizal (EcM) fungi, play vital roles in modulating PSFs by mediating plant–soil interactions. However, global patterns of PSFs in relation to mycorrhizal type remain poorly understood. Location Global. Time Period 1994–2022. Major Taxa Studied Woody species. Methods We conducted a meta‐analysis of published data to investigate the difference in the global expression of PSFs between EcM and AM woody plant hosts. Results Our results show that EcM hosts generally experience positive PSFs, whereas AM hosts generally experience negative PSFs, a difference that is consistent across angiosperm and gymnosperm woody plant species. The difference in the mean effect size of PSFs between EcM and AM hosts was strongest for studies conducted in North America and Asia, and was not significant for studies conducted in Europe and Oceania. AM woody species displayed more negative PSFs in wet and cool regions, whereas EcM woody species showed no latitudinal or climatic gradients in the strength of PSFs. These trends resulted in a convergence in the effects of PSFs on EcM and AM woody plants among studies conducted in the tropics, and a significant divergence in temperate and boreal studies. The meta‐analysis also revealed that the expression and detection of PSFs in both AM and EcM woody species are affected by the experimental setting. Main Conclusions Our findings highlight the importance of mycorrhizal type in shaping PSFs and their implications for plant community assembly and dynamics in different biogeographic settings. We discuss how experimental designs influence the detection of PSFs and suggest appropriate methods for future studies.